Teacher Professionalism Attitude (Historical, Genealogical and Conceptual) - Bariroh Nilna Riska; Mumtaza Fitriyatin; Saheed Adewale Mikael (Yayasan Dinamika Ilmu Banyuwangi, 2025)
Teacher professionalism is a fundamental aspect in the world of education that influences the quality of learning and student development. This study examines teacher professionalism from three main perspectives: historical, genealogical, and conceptual. Historically, teacher professionalism has developed along with changes in the education system, policies, and social demands. From a genealogical perspective, the concept of teacher professionalism is formed through the interaction between scientific traditions, social norms, and educational policies that continue to develop. Conceptually, teacher professionalism includes pedagogical, personality, social, and professional competencies that are standards in educational practice. This study aims to describe the dynamics of the development of teacher professionalism and formulate an ideal concept for teachers in carrying out their duties professionally in accordance with the demands of the times.